New Firms and Free Enterprise (Book). - Miller, Herbert E.; Dugan, James E. (The Accounting Review, 1945)
Reviews the book "New Firms and Free Enterprise: Pre-War and Post-War Aspects," by Alfred R. Oxenfeldt.